Acyl radical cascade reactions: the synthesis of azasteroids - Double, Philip John (1998)
Our work has been concerned with the synthesis of azasteroid ring systems, utilising acyl radical cascade reactions. Chapter 1 comprises an overview of published work relevant to our studies: an analysis of steroid biosynthesis and synthesis; a review of the use of azasteroids, their biological activity and current synthetic techniques in azasteroid formation. This initial chapter also includes an introduction to published work in the area of nitrogen heterocycle synthesis using radical reactions and finally the use of acyl radicals in synthesis, particularly cascade reactions.